Immunological role of chlorogenic acid in broiler intestinal health under chronic heat stress - Aftab Shaukat; Sana Hanif; Rizwan Shukat; Muhammad Tahir Aleem; Irfan Shaukat; Mikhlid H. Almutairi; Bader O. Almutairi; Mubashar Hassan; Shahid Ali Rajput; Shu-cheng Huang; Kasim Sakran Abass; Ren-Wei Su (Poultry Science)
The study aims to investigate the immunological role of chlorogenic acid (CA) on the intestinal health of broiler under chronic heat stress. 240 broilers were randomly divided into 4 groups: control group with a feeding temperature of (22 ± 2) °C, and the other three groups with a feeding temperature of (30 ± 2) °C. The chronic heat stress group (HS group) was fed with the basic diet daily, while the high-dose CA groups (HCA group) and low-dose (LCA group) were supplemented with CA at 600 mg/kg and 300 mg/kg, respectively. The health performance, intestinal antioxidant indicators, inflammatory factors, heat shock proteins, and barrier integrity-related protein expression were tested. The results showed that 600 mg/kg CA in the basic diet was promoted the morphological and cellular performance of intestinal epithelial cells of heat-stressed broilers and significantly increased the ADG (P < 0.05). HCA significantly improved the activity of SOD and CAT in the intestinal tract of heat-stressed broilers (P < 0.05), and significantly reduced the content of peroxides MDA (P < 0.05). HCA significantly inhibited the concentration of IL-1β, IL-6, and TNF-α (P < 0.05), significantly increased the content of IL-10 (P < 0.05). Further, HCA significantly downregulated the proteins and genes expression of HSP27, HSP70, and HSP90 (P < 0.05), and significantly upregulated the proteins and genes expression of Claudin1, Occludin, and ZO-1 (P < 0.05), thereby promoting intestinal barrier integrity. These findings highlight the potential of CA as a functional additive to mitigate the adverse effects of heat stress in poultry production.